Urethane resin composition

A urethane resin composition for building insulation, using a specific set of components without foam stabilizers or surface conditioners, addresses swelling and adhesion issues, enhancing fire safety and cost-effectiveness.

JP2025013693AActive Publication Date: 2025-01-24NIPPON AQUA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024198189
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-24
Estimated Expiration
2042-01-18

Smart Images

  • Figure 2025013693000001
    Figure 2025013693000001
  • Figure 2025013693000002
    Figure 2025013693000002
  • Figure 2025013693000003
    Figure 2025013693000003
Patent Text Reader

Abstract

To provide an urethane resin composition which prevents swelling during heating.SOLUTION: An urethane resin composition for forming a foam constituting a heat insulation material of a building contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a foaming agent and a flame retardant, and does not contain a foam stabilizer and a surface control agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a urethane resin composition for use as a heat insulating material for buildings. [Background technology]

[0002] In reinforced concrete and steel construction homes, sprayed rigid polyurethane foam insulation is often used to prevent condensation, provide insulation, and save energy. In recent years, there have been rare cases of fires caused by insulation ignition due to improper construction management, etc. In addition, even when a general fire occurs, the fire may spread to insulation and cause the fire to spread. In order to prevent such urethane foam from burning, a fire-resistant coating (such as a cement-based inorganic spray material) is sometimes applied, but problems remain, such as the time required for application and the fact that the coating does not adhere well to the urethane foam after application, leading to the coating falling off.

[0003] As such, urethane resin compositions having flame retardancy are known, as disclosed in the following Patent Documents 1 and 2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6200435 [Patent Document 2] Patent No. 6725606 Summary of the Invention [Problem to be solved by the invention]

[0005] In the heat generation test conforming to ISO-5660 for evaluating the flame retardancy of a urethane resin composition, a testing device called a cone calorimeter is used. The cone calorimeter is equipped with a cone heater placed above a test specimen cut to a predetermined size, and a spark rod provided between the test specimen and the cone heater. In the heat generation test in accordance with ISO-5660, combustible gas is generated from the test specimen by heating it with a cone heater, and the combustible gas is ignited by a spark from a spark rod to cause combustion. The total amount of heat generated by the combustion is measured using a specified measurement method, and the flame retardancy is evaluated in light of the performance requirements shown in Table 1 below. These performance requirements have been established by the General Building Research Corporation of Japan and the Construction Materials Testing Center as standards for conforming to the technical standards stipulated in Article 2, item 9 of the Building Standards Act, Article 1, items 5 and 6 of the Enforcement Order of the Building Standards Act, and Article 108-2 of the Enforcement Order of the Building Standards Act.

[0006] [Table 1] JPEG2025013693000001.jpg38153

[0007] When conducting heat generation tests, some of the test specimens swelled when heated by the cone heater, and in some cases the swollen parts of the test specimens came into contact with the spark plug, or discharges were confirmed even without the expanded test specimen coming into contact with the plug (these phenomena are hereinafter referred to as "spark contact"). Test specimens in which spark contact has occurred will not produce valid results when conforming to ISO-5660, so it is necessary to check each time for the presence or absence of spark contact.

[0008] Furthermore, when the urethane resin composition is used as a heat insulating material, there is a problem in that the expansion caused by heating applies pressure to interior materials (such as gypsum boards) provided around the heat insulating material, causing damage. If the interior materials are damaged, heat from a fire will be more easily transferred to the insulation, increasing the possibility that the heat will have an adverse effect on the exterior materials as well.

[0009] Therefore, one of the objects of the present invention is to provide a urethane resin composition that is less likely to blister when heated. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides a urethane resin composition that forms a foam that constitutes a thermal insulation material for buildings, which contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a blowing agent, and a flame retardant, but does not contain a foam stabilizer or a surface conditioner. Effect of the Invention

[0011] According to the present invention, a urethane resin composition that is less likely to blister when heated can be obtained. In a preferred embodiment of the present invention, a urethane resin composition can be obtained that does not cause spark contact even in a heat generation test according to ISO-5660. Furthermore, in a preferred embodiment of the present invention, a urethane resin composition can be obtained that, when used as an insulating material for buildings, prevents the insulating material from expanding beyond the clearance between the insulating material and the interior material, and does not push up and damage the interior material. Furthermore, in a preferred embodiment of the present invention, the number of raw materials required to form the urethane resin composition can be reduced, thereby contributing to cost reduction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <1> Overall Configuration The urethane resin composition according to the present invention is for forming a foam that constitutes a thermal insulation material for buildings, and contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a blowing agent, and a flame retardant, but does not contain a foam stabilizer or a surface conditioner. The urethane resin composition according to the present invention may further contain a material derived from a mineral such as a clay mineral. The above composition is separated into the polyisocyanate compound (first liquid) and the other components (second liquid), and the two are mixed while being sprayed, or the two are mixed and sprayed, etc., to form an insulating layer on a building.

[0013] <2> About various performance The urethane resin composition according to the present invention can be provided with the following properties by adjusting the blending ratio of each material.

[0014] <2.1> Non-flammable performance The urethane resin composition according to the present invention can be provided with non-flammability as specified by a heat generation test in accordance with the ISO-5660 test.

[0015] <2.1.1> About ISO-5660 Testing In heat generation tests conforming to ISO-5660, a test device called a cone calorimeter is used. The cone calorimeter is equipped with a cone heater that is placed above a test specimen cut to a specified size, and a spark rod that is installed between the test specimen and the cone heater. Combustible gas is generated from the test specimen when heated by the cone heater, and the combustible gas is ignited by a spark from the spark rod, causing combustion. The total heat generated by the combustion is measured using a specified measurement method, and the flame retardancy is evaluated in accordance with the performance requirements shown in Table 2 below.

[0016] [Table 2] JPEG2025013693000002.jpg38153

[0017] <2.2> Swelling during heating (maximum expansion length) The urethane resin composition according to the present invention can achieve a swelling amount that does not cause spark contact when the ISO-5660 test is carried out. The guideline for preventing spark contact is that the maximum expansion length in the height direction of the test specimen should be less than 8 mm, more preferably 2 mm or less. The above configuration makes it possible to avoid spark contact and obtain valid results for ISO-5660 testing.

[0018] <2.2.1> Measurement method for swelling amount The method for measuring the amount of swelling in the height direction of the test specimen will be described below. (1) Before conducting the heat generation test, the height position of the top surface of the test specimen is marked on the windshield glass frame attached to the front of the cone calorimeter. (2) After the heat generation test, visually measure the height from the marking on the windshield frame to the highest point on the top surface of the expanded test specimen.

[0019] <2.3> Density The urethane resin composition according to the present invention can provide a foam having a density of 30 kg / m3 or more. By making the density of the foam 30 kg / m3 or more, it is possible to obtain a sufficient deformation suppression effect against external impacts when used as a thermal insulation material for buildings.

[0020] <3> Polyisocyanate Compounds The polyisocyanate compound is a material used as a base agent in the urethane resin composition according to the present invention. Examples of the polyisocyanate compound include aromatic polyisocyanates, alicyclic polyisocyanates, aliphatic polyisocyanates, and modified polyisocyanates. Examples of the aromatic polyisocyanate include phenylene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate. Examples of the alicyclic polyisocyanate include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate. Examples of the aliphatic polyisocyanate include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate. The modified polyisocyanate is an isocyanate-terminated prepolymer obtained by reacting a polyol component with a polyisocyanate compound, and examples of the modified polyisocyanate include urethane modified products, carbodiimide modified products, urea modified products, biuret modified products, and allophanate modified products. The polyisocyanate compounds may be used alone or in combination. In particular, polymethylene polyphenyl polyisocyanate (polymeric MDI, crude MDI) is preferred because it is liquid at room temperature and is easily available. Examples of the polymethylene polyphenyl polyisocyanate include Millionate MR-200, MR-100, and MR-400 manufactured by Tosoh Corporation, Sumidur 44V20L and Dismodur 44V20L manufactured by Covestro Corporation, PM-200 and PM-400 manufactured by Wanhua Chemical Industry Co., Ltd., and PAPI27 and PAPI135 manufactured by DOW Corporation.

[0021] The amount of polyisocyanate contained in the urethane resin composition is preferably adjusted so that the isocyanate index is 150 to 1000. If it is 150 or more, the flame retardancy is further improved, and if it is 1000 or less, the adhesion to the framework and the like is good. In particular, in the present invention, the isocyanate index is most preferably in the range of 400 to 600. The isocyanate index is calculated as the equivalent ratio of the isocyanate group contained in the isocyanate component to the active hydrogen contained in the polyol component and the water or the like of the blowing agent. [Isocyanate group] / [OH group] (molar ratio) x 100

[0022] <4> Polyol Compounds The polyol compound is a material used as a curing agent in the urethane resin composition according to the present invention. The polyol compound comprises an ester-based polyol compound or an ether-based polyol compound, or a combination thereof.

[0023] <4.1> Ester polyol compounds Examples of the ester-based polyol compound include polymers obtained by dehydration condensation of polybasic acids and polyhydric alcohols, polymers obtained by ring-opening polymerization of lactones such as ε-caprolactone and α-methyl-ε-caprolactone, and condensates of hydroxycarboxylic acids and the above-mentioned polyhydric alcohols. Specific examples of the polybasic acid include adipic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, succinic acid, etc. In terms of flame retardancy, terephthalic acid modification is preferred.

[0024] <4.2> Other polyol compounds Examples of the other polyol compounds include polylactone polyols, polycarbonate polyols, aromatic polyols, alicyclic polyols, aliphatic polyols, polymer polyols, and polyether polyols. Examples of the polylactone polyol include polypropiolactone glycol, polycaprolactone glycol, and polyvalerolactone glycol. Examples of the polycarbonate polyol include polyols obtained by dealcoholization reaction of a hydroxyl group-containing compound such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, or nonanediol with diethylene carbonate, dipropylene carbonate, or the like. Examples of the aromatic polyol include bisphenol A, bisphenol F, phenol novolac, and cresol novolac. Examples of the alicyclic polyol include cyclohexanediol, methylcyclohexanediol, isophoronediol, dicyclohexylmethanediol, and dimethyldicyclohexylmethanediol. Examples of the aliphatic polyol include ethylene glycol, propylene glycol, butanediol, pentanediol, and hexanediol. Examples of the polyhydric polyether polyol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, diethylene glycol, dipropylene glycol, neopentyl glycol, and cyclohexane-1,4-diol. Examples of the polyether polyol include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide using as an initiator a compound having two or more, preferably 3 to 8 active hydrogen groups, such as low molecular weight polyols such as bisphenol A, bis(β-hydroxyethyl)benzene, xylylene glycol, glycerin, trimethylolpropane, pentaerythritol, and sucrose, and aromatic and aliphatic polyamines such as ethylenediamine, propylenediamine, toluenediamine, metaphenylenediamine, diphenylmethanediamine, xylylenediamine, and triethanolamine, and alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide; and polyether polyols obtained by ring-opening polymerization of cyclic ether monomers such as alkyl glycidyl ethers such as methyl glycidyl ether, aryl glycidyl ethers such as phenyl glycidyl ether, and tetrahydrofuran. In addition, polyether polyols containing bromine, phosphorus, etc. may also be used.

[0025] <5> Mineral-based materials Mineral-based materials are materials intended to provide increased flame retardancy and increased density. As the mineral-derived material, silicate compounds are preferred, and examples of the mineral-derived material that can be used include montmorillonite, saponite, hectorite, vermiculite, kaolinite, mica, and talc. An example of the material containing kaolinite as a main component is kaolin. The kaolin also includes calcined kaolin obtained by treating kaolin at high temperatures. Calcined kaolin is preferable because it has a small moisture content and a small particle size distribution.

[0026] The content of the mineral-derived material is not particularly limited, but is preferably 15 to 85 parts by weight based on 100 parts by weight of the polyol compound.

[0027] <6> trimerization catalyst The trimerization catalyst is a material that promotes the reaction of isocyanate groups contained in a polyisocyanate compound to cause trimerization and the formation of isocyanurate rings. Examples of the trimerization catalyst that can be used include nitrogen-containing aromatic compounds such as tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, and 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine; alkali metal salts of carboxylates such as potassium acetate, potassium 2-ethylhexanoate, and potassium octylate; and quaternary ammonium salts such as tetramethylammonium salts, tetraethylammonium salts, and tetraphenylammonium salts. From the standpoint of adhesion at low temperatures and flame retardancy, a combination of an alkyl metal carboxylate and a quaternary ammonium salt is desirable. Examples of trimerization catalysts include Toyocat-TRX, Toyocat-TRV, and Toyocat-TR20 manufactured by Tosoh; DABCO TMR, DABCO TMR-2, DABCO TMR-7, DABCO K-15, UCAT 18X, and Polycat 46 manufactured by Evonik; and KAOLIZER NO. 410 and KAOLIZER NO. 420 manufactured by Kao.

[0028] The content of the trimerization catalyst is not particularly limited, but is preferably 1 to 20 parts by weight per 100 parts by weight of the polyol compound. When it is 1 part by weight or more, the flame retardancy is further improved, and when it is 20 parts by weight or less, problems such as clogging of the mixing part of the spray gun due to too fast reaction can be suppressed.

[0029] <7> Foaming Agent The foaming agent is a material that promotes a decrease in density of the molded product by generating gas inside the resin when the polyisocyanate compound (first liquid) is mixed with the other components (second liquid). An example of the blowing agent is water. Carbon dioxide is generated by the reaction of isocyanate with water, and the carbon dioxide is trapped inside the foam, promoting a decrease in the density of the molded product.

[0030] Other examples of foaming agents include the so-called physical foaming agents listed below. Although they are liquid at room temperature, they gasify inside the resin due to the exothermic reaction between isocyanate and polyol, promoting a decrease in density of the molded product.

[0031] [1] Hydrocarbon compounds Propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, methyl formate, and the like.

[0032] [2] Chlorinated aliphatic hydrocarbon compounds Dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, isopentyl chloride and the like.

[0033] [3] Fluorine compounds CHF3, CH2F2, CH3F etc.

[0034] [4] Hydrochlorofluorocarbon compounds Trichloromonofluoromethane, trichlorotrifluoroethane, dichloromonofluoroethane (for example, HCFC141b (1,1-dichloro-1-fluoroethane), HCFC22 (chlorodifluoromethane), HCFC142b (1-chloro-1,1-difluoroethane)), and the like.

[0035] [5] Hydrofluorocarbon HFC-245fa (1,1,1,3,3-pentafluoropropane) made by Central Glass, HFC-365mfc (1,1,1,3,3-pentafluorobutane) made by Honeywell, etc.

[0036] [6] Hydrofluoroolefin Honeywell Solstice LBA (HFO-1233zd, (E)-1-chloro-3,3,3-trifluoropropene), Chemours Opteon 1100 (HFO-1336mzz(Z), (Z)-1,1,1,4,4,4-hexafluoro-2-butene), Chemours Opteon 1150 (HFO-1336mzz(E), (E)-1,1,1,4,4,4-hexafluoro-2-butene), AGC Amorea 1224yd ((Z)-1-chloro-2,3,3,3-tetrafluoropropene), etc.

[0037] [7]Organic compounds Methyl formate, diisopropyl ether, and the like.

[0038] Other examples of the foaming agent that can be used include nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas, which can be dispersed or dissolved in the polyol component or isocyanate component.

[0039] The content of the foaming agent is not particularly limited, but is preferably 1 to 100 parts by weight per 100 parts by weight of polyol. The more parts by weight of the foaming agent, the lower the foam density, but at the same time, the lower the dimensional stability and compressive strength. Therefore, the number of parts by weight of the foaming agent should be set according to the density design.

[0040] In the present invention, the above-mentioned foaming agents may be used alone or in combination.

[0041] <8> Flame retardants The flame retardant is a material for imparting flame retardancy to the urethane resin composition according to the present invention. In the present invention, the flame retardant is not particularly limited, but is preferably one containing at least one selected from the group consisting of red phosphorus, ammonium polyphosphate, and phosphoric ester, in order to obtain high flame retardancy. In particular, a combination of two or more components, such as ammonium polyphosphate and / or a phosphoric ester, in addition to red phosphorus is preferred in that even higher flame retardancy can be obtained.

[0042] <8.1> Red phosphorus Red phosphorus is a material that reduces the total amount of heat generated during combustion. There is no limitation on the red phosphorus used in the present invention, and a commercially available product can be appropriately selected and used.

[0043] The content of the red phosphorus is not particularly limited, but it is preferable that the content of the red phosphorus is 15 parts by weight to 35 parts by weight based on 100 parts by weight of the polyol compound.

[0044] <8.2> Phosphate-containing flame retardants Phosphate-containing flame retardants, like red phosphorus, are materials that are used to reduce the total amount of heat generated during combustion. The phosphate-containing flame retardant used in the present invention contains phosphoric acid.

[0045] Examples of the phosphate-containing flame retardant include phosphates consisting of salts of the various phosphoric acids and at least one metal or compound selected from metals in Groups IA to IVB of the periodic table, ammonia, aliphatic amines, and aromatic amines. Examples of the metals in Groups IA to IVB of the periodic table include lithium, sodium, calcium, barium, iron (II), iron (III), and aluminum. Examples of the aliphatic amine include methylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, and piperazine. Examples of the aromatic amine include pyridine, triazine, melamine, and ammonium. The above phosphate-containing flame retardants may be subjected to known water resistance improving treatments such as treatment with a silane coupling agent or coating with a melamine resin, and known foaming assistants such as melamine and pentaerythritol may be added.

[0046] Specific examples of the phosphate-containing flame retardant include monophosphates, pyrophosphates, and polyphosphates. Examples of the monophosphate salts include ammonium salts such as ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; lithium salts such as monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite, dilithium phosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, tribarium phosphate, and barium hypophosphite; magnesium salts such as monohydrogen magnesium phosphate, magnesium hydrogen phosphate, trimagnesium phosphate, and magnesium hypophosphite; calcium salts such as calcium dihydrogen phosphate, calcium hydrogen phosphate, tricalcium phosphate, and calcium hypophosphite; and zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite. Examples of the polyphosphate include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, and aluminum polyphosphate.

[0047] Among these, it is preferable to use polyphosphates since they improve the self-extinguishing properties of the phosphate-containing flame retardant, and it is more preferable to use ammonium polyphosphate or aluminum phosphite, which forms a foam layer when heated.

[0048] The phosphate-containing flame retardants may be used alone or in combination.

[0049] The content of the phosphate-containing flame retardant is not particularly limited, but is desirably 20 parts by weight to 50 parts by weight based on 100 parts by weight of the polyol compound.

[0050] <8.3> Chlorine-containing flame retardants The chlorine-containing flame retardant is an element that suppresses the maximum heat release rate in the early stage of combustion. The following five types of chlorine-containing flame retardants are commonly used: (a) Tris(chloroethyl)phosphate (TCEP) (b) Tris(β-chloropropyl)phosphate (TCPP) (c) Tris(dichloropropyl)phosphate (TDCP) (d) Tetrakis(2-chloroethyl)dichloroisopentyl diphosphate (V6) (e) Polyoxyalkylene bis(dichloroalkyl) phosphate (CR-504L)

[0051] The content of the chlorine-containing flame retardant is not particularly limited, but is preferably 60 to 120 parts by weight based on 100 parts by weight of the polyol compound.

[0052] <9> Foam stabilizers and surface conditioners The foam stabilizers and surface conditioners not included in the formulation of the present invention will be explained below.

[0053] <9.1> Foam stabilizer The foam stabilizer is an organosiloxane-polyoxyalkylene copolymer used in the production of polyurethane foam. Examples of foam stabilizers include L-6900 manufactured by MOMENTIVE and SH-193 manufactured by Dow Corning Toray.

[0054] <9.2> Surface conditioners A surface conditioner is an additive that acts as a defoamer, leveling agent, and anti-foaming agent by controlling surface tension, thereby forming a good coating film. Examples of the surface conditioner include acrylic polymers such as SEI-W01 and SEI-1501 manufactured by Kusumoto Chemicals.

[0055] <10> others In addition, the urethane resin composition according to the present invention may contain the following materials as appropriate.

[0056] <10.1> Catalyst The catalyst used in the formation of urethane foam is a material that promotes the reaction between the isocyanate and the active hydrogen in the polyol, and the reaction between the isocyanate and water.

[0057] Examples of catalysts having an amine group include N-alkyl polyalkylene polyamines such as triethylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, and N,N,N',N'-tetramethylethylenediamine, N'-(2-hydroxyethyl)-N,N,N'-trimethylethylenediamine, 1-(2-dimethylaminoethyl)-4-methylpiperazine, 1,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, N-methylmorpholine, N-ethylmorpholine, N,N-dimethylaminoethylmorpholine, dimethylcyclocyclohexylamine, dimethylethanolamine, dimethylaminohexanol, dimethylaminoethoxyethanol, and diazabicycloundecene. Examples of catalysts containing an organic metal include bismuth octylate, lead octylate, tin(II) 2-ethylhexanoate, dibutylbis[(1-oxooctyl)oxy]stannane, dibutyltin diacetate, and dibutyltin dilaurate.

[0058] Examples of amine catalyst products include Tosoh's TEDA-L33, TOYOCAT-ET, TOYOCAT-MR, TOYOCAT-TE, TOYOCAT-DT, TOYOCAT-NP, RX-5, RX-10, TOYOCAT-DM70, Evonik's DABCO 33LV, DABCO BL-19, DABCO BL-11, DABCO DMEA, DABCO T, DABCO. N-MM, DABCO N-EM, DABCO NO.26, KAOLIZER NO.120, KAOLIZER Examples include NO.300, KAOLIZER NO.350, and KAOLIZER NO.390. These catalysts may be used either individually or in combination. EXAMPLES

[0059] <1> Test conditions The following tests were carried out on the foam made of the urethane resin composition according to the present invention. Details of each material are as follows.

[0060] (1) Polyol compounds A: Terephthalic acid polyester polyol (manufactured by Air Water Material, product name: Maximol RFK-505, hydroxyl value = 250mgKOH / g)

[0061] (2) Foam stabilizer B: Silicone foam stabilizer (Momentive, product name: L-6900)

[0062] (3) Surface conditioner C: Acrylic polymer (Kusumoto Chemicals, product name: SEI-W01)

[0063] (4) Catalyst D1: Amine catalyst (manufactured by Evonik, product name: DABCO 2040) D2: Amine catalyst (manufactured by Evonik, product name: Polycat201) D3: Organometallic catalyst (Shepherd, product name: Bicat 8210)

[0064] (5) Trimerization catalyst E1: Quaternary ammonium salt (manufactured by Evonik, product name: TMR-7) E2: Potassium acetate catalyst (manufactured by Evonik, product name: Polycat46)

[0065] (6) Mineral-derived materials F: Calcined kaolin (manufactured by Imerys Minerals, product name: Glomax LL)

[0066] (7) Flame retardants G1: Red phosphorus (manufactured by Rinkagaku Kogyo Co., Ltd., product name: Nova Excel 140) G2: Ammonium polyphosphate (manufactured by Taihei Chemical Industry Co., Ltd., product name: Taien CII) G3: Phosphate ester (manufactured by Wansheng, product name: TCPP)

[0067] (8) Foaming agent H1: HFO-1233zd (Honeywell, product name: Solstice LBA) H2: HFO-1336mzz (manufactured by Chemours, product name: Opteon1100) H3: Water (hydroxyl value = 6234 mg KOH / g)

[0068] (9) Polyisocyanate I: Polymeric MDI (manufactured by Tosoh Corporation, product name: Millionate MR-200, NCO content = 31%)

[0069] <2> Test specimen preparation method According to the formulations in the tables of each figure, the polyol, catalyst, trimerization catalyst, flame retardant, foaming agent, surface conditioner, and foam stabilizer components were weighed out into a 1000 mL polypropylene beaker and mixed. Hereinafter, this mixture will be referred to as a polyol premix. The polyol premix and isocyanate were thermostated at 5°C. The isocyanate component was added to the temperature-adjusted polyol premix component according to the formula in the table of each figure. After stirring for about 3 seconds with a hand mixer, the mixture was quickly poured into a 200 x 200 x 200 mm wooden box that had been adjusted to 20°C, obtaining a foam. (Since the polyol premix component contains powder, the isocyanate component was pre-mixed and dispersed immediately before mixing.) After curing for 24 hours after foaming, the foam was cut into pieces measuring 99mm x 99mm x 50mm, and the mass was measured (the foam density was calculated from the mass and size obtained), after which a cone calorie test specimen was created (the test specimen was cut to a height of 50mm in the foaming direction).

[0070] <3> Exam Content Each specimen was subjected to a heat generation test conforming to the ISO-5660 test method, with a radiant heat intensity of 50 kW / m2 and a heating time of 20 minutes, and an evaluation was performed on the total heat generation (after 10 minutes of heating and after 20 minutes of heating), maximum heat generation rate, time exceeding 200 kW / m2 (time during which the maximum heat generation rate continuously exceeded 200 kW / m2), maximum expansion length of the specimen (in the height direction), and whether or not there was contact with sparks, etc. Details of the test equipment used in this test are as follows: -Manufactured by Toyo Seiki Seisakusho, Product name: Cone calorimeter, Model: C4 Distance between test piece and spark plug: 12.5mm

[0071] <4> Test results The following description will be given with reference to the figures in which experimental examples for comparison are extracted from all test results.

[0072] (1) Experimental Examples 1 and 2 (Table 3) [When either a foam stabilizer or a surface conditioner is included] In Experimental Examples 1 and 2 (Table 3), the formulations contained either a foam stabilizer or a surface conditioner.

[0073] [Table 3] JPEG2025013693000003.jpg189164

[0074] Spark contact occurred in all test specimens.

[0075] (2) Experimental Examples 3 to 21 (Tables 4 to 7) [When the amount of kaolinite is changed] In Experimental Examples 3 to 21 (Tables 4 to 7), no foam stabilizer or surface conditioner was included, and the amount of kaolinite blended was varied from 0 parts by weight to 100 parts by weight.

[0076] [Table 4] JPEG2025013693000004.jpg142164

[0077] [Table 5] JPEG2025013693000005.jpg142164

[0078] [Table 6] JPEG2025013693000006.jpg142164

[0079] [Table 7] JPEG2025013693000007.jpg154164

[0080] The maximum expansion length of all test specimens was 2 mm or less, and no spark contact occurred. Moreover, in Experimental Examples 3, 4, 20, and 21, the test pieces were equivalent to quasi-noncombustible materials, while in Experimental Examples 5 to 19 (in which the amount of kaolinite blended was 15 parts by weight to 85 parts by weight), the test pieces were equivalent to noncombustible materials. Moreover, in the test specimens according to Experimental Examples 4 to 21 (in which the amount of kaolinite blended was 10 parts by weight to 100 parts by weight), the foam density was 30 kg / m3 or more.

[0081] (3) Experimental Examples 22 to 32 (Tables 8 to 10) [When the amount of flame retardant is changed] In Experimental Examples 22 to 32 (Tables 8 to 10), no foam stabilizer or surface conditioner was included, the amount of kaolinite was fixed at 25 parts by weight, and the amount of flame retardant was changed.

[0082] [Table 8] JPEG2025013693000008.jpg154164

[0083] [Table 9] JPEG2025013693000009.jpg154164

[0084] [Table 10] JPEG2025013693000010.jpg168164

[0085] The maximum expansion length of all test specimens was 2 mm or less, and no spark contact occurred. Moreover, the test specimens according to Experimental Examples 23 to 26 and Experimental Examples 29 to 32 were equivalent to noncombustible materials, and had a foam density of 30 kg / m3 or more.

[0086] (4) Experimental Examples 33 to 40 (Tables 11 and 12) [When the amount of foaming agent is changed] In Experimental Examples 33 to 40 (Tables 11 and 12), no foam stabilizer or surface conditioner was included, and the amount of kaolinite was 0 parts by weight, 25 parts by weight, 50 parts by weight, and 75 parts by weight, while the amount of each foaming agent was changed.

[0087] [Table 11] JPEG2025013693000011.jpg154164

[0088] [Table 12] JPEG2025013693000012.jpg154164

[0089] The maximum expansion length of all test specimens was 2 mm or less, and no spark contact occurred. Moreover, in Experimental Examples 33 and 40, the materials were equivalent to quasi-noncombustible materials, and in Experimental Examples 34 to 39, the materials were equivalent to noncombustible materials. In addition, the foam density of all test specimens was 30 kg / m3 or higher.

Claims

1. A urethane resin composition for forming a foam constituting a thermal insulation material for a building, The composition is characterized by comprising at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a foaming agent, and a flame retardant, and is free of a foam stabilizer and a surface conditioner. Urethane resin composition.

2. Further comprising a mineral-derived material. The urethane resin composition according to claim 1.

3. The mineral-derived material is kaolinite. The urethane resin composition according to claim 2.

4. The kaolinite is calcined kaolin. The urethane resin composition according to claim 3.

5. The calcined kaolin is contained in an amount of 15 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of the polyol compound, and the isocyanate index is 400 to 600. The urethane resin composition according to claim 4.

6. The foam is characterized in that it has quasi-nonflammability in a heat generation test in accordance with ISO-5660. The urethane resin composition according to claim 1 .

7. The foam is characterized in that it is non-flammable in a heat generation test in accordance with ISO-5660. The urethane resin composition according to claim 1 .

8. The maximum expansion length in the height direction of the test specimen during a heat generation test in accordance with ISO-5660 is less than 8 mm. The urethane resin composition according to claim 1 .

9. The maximum expansion length in the height direction of the test specimen during a heat generation test in accordance with ISO-5660 is 2 mm or less. The urethane resin composition according to claim 8.

10. The flame retardant contains at least one selected from the group consisting of red phosphorus, ammonium polyphosphate, and phosphoric acid ester. The urethane resin composition according to claim 1 .

11. The density of the foam is 30 kg / m 3 The above is characterized in that The urethane resin composition according to claim 1 .

Citation Information

Patent Citations

  • Wall covering material

    JP2004043983A

  • Flame retardant thermoplastic resin composition

    JP2010024272A

  • Vinyl chloride resin composition, insulated wire prepared using the same, and method of producing insulated wire

    JP2015147845A

  • Foamable composition for flame-retardant polyurethane foam

    JP2020007386A

  • Electrolytic capacitor

    JP2020088329A